Bone‐specific alkaline phosphatase and bone turnover in African American hemodialysis patients. Issue 1 (27th June 2016) - Yessayan, Lenar; Moore, Carol; Lu, Mei; Yee, Jerry
Abstract: Introduction: Noninvasive measures of bone activity include intact parathyroid hormone (iPTH) and bone‐specific alkaline phosphatase (BSAP). Whether BSAP measurement alone or in combination with other biochemical data provides more reliable information about bone turnover than iPTH alone in African Americans on hemodialysis is unknown.Methods: This cross‐sectional study aimed to determine the optimal predictor and cutoff points for BSAP, iPTH, calcium and phosphorus in classifying bone biopsy findings. Forty‐three African American hemodialysis patients were available for analysis. Biochemical data on the day of biopsy across a spectrum of qualitative histologic bone features were compared. Classification and regression tree analysis was used to determine both the optimal predictor and cutoff points for BSAP, iPTH, calcium and phosphorus in identifying bone turnover status.Findings: Seven subjects had adynamic disease, 31 had mild/moderate hyperparathyroid bone features, and five had severe hyperparathyroid bone disease. BSAP was the optimal predictor of bone biopsy with a cutoff point of 22 ng/mL. Calcium and phosphorus had no predictive value. At BSAP ≤ 22 ng/mL, subjects had either adynamic bone disease or mild/moderate hyperparathyroid bone disease but iPTH was not useful in further classifying biopsy findings. When BSAP was >22 ng/mL, subjects had either mild/moderate or severe hyperparathyroid bone disease, and iPTH was useful in further classifying biopsy findings. With BSAP > 22 ng/mL and iPTH < 726 pg/mL, all subjects had mild/moderate bone turnover features.Discussion: Compared to iPTH, BSAP was shown to be the optimal predictor of biopsy findings with an optimal cutoff at 22 ng/mL.